Patient preferences toward an interactive e-consent application for research using electronic health records. (19th December 2017) - Harle, Christopher A; Golembiewski, Elizabeth H; Rahmanian, Kiarash P; Krieger, Janice L; Hagmajer, Dorothy; Mainous, Arch G; Moseley, Ray E
Abstract: Objective: The purpose of this study was to assess patient perceptions of using an interactive electronic consent (e-consent) application when deciding whether or not to grant broad consent for research use of their identifiable electronic health record (EHR) information. Materials and Methods: For this qualitative study, we conducted a series of 42 think-aloud interviews with 32 adults. Interview transcripts were coded and analyzed using a modified grounded theory approach. Results: We identified themes related to patient preferences, reservations, and mixed attitudes toward consenting electronically; low- and high-information-seeking behavior; and an emphasis on reassuring information, such as data protections and prohibitions against sharing data with pharmaceutical companies. Participants expressed interest in the types of information contained in their EHRs, safeguards protecting EHR data, and specifics on studies that might use their EHR data. Discussion: This study supports the potential value of interactive e-consent applications that allow patients to customize their consent experience. This study also highlights that some people have concerns about e-consent platforms and desire more detailed information about administrative processes and safeguards that protect EHR data used in research. Conclusion: This study contributes new insights on how e-consent applications could be designed to ensure that patients' information needs are met when seeking consent for research use of health record information. Also, this study offers a potential electronic approach to meeting the new Common Rule requirement that consent documents contain a "concise and focused" presentation of key information followed by more details.